Mathematics Lesson Study Around the World Theoretical and Methodological Issues (ICME-13 Monographs,, 2018)
This book introduces the specifics of mathematics lesson study with regard to regional/national particularities, discussing the methodological and theoretical tools that can be used to pursue research on lesson study (its forms, contents, effects etc.) from an international perspective. Lesson study and learning study (LS) are becoming increasingly important in teacher education, mostly in continuous professional development, but also in prospective teachers' education, and this interest is accompanied by a demand for more solid theorization of the lesson study process. A number of social, cultural, cognitive and affective issues are reflected in the way LS develops, and the book examines the latest results of these developments.